Oral morphine dosing predictions based on single dose in healthy children undergoing surgery. Issue 1 (25th October 2016) - Dawes, Joy M.; Cooke, Erin M.; Hannam, Jacqueline A.; Brand, Katherine A.; Winton, Pamela; Jimenez‐Mendez, Ricardo; Aleksa, Katarina; Lauder, Gillian R.; Carleton, Bruce C.; Koren, Gideon; Rieder, Michael J.; Anderson, Brian J.; et al.
Abstract: Background: Oral morphine has been proposed as an effective and safe alternative to codeine for after‐discharge pain in children following surgery but there are few data guiding an optimum safe oral dose. Aims: The aim of this study was to characterize the absorption pharmacokinetics of enteral morphine in order to simulate time–concentration profiles in children given common oral morphine dose regimens. Methods: Children (2–6 years, n = 34) undergoing elective surgery and requiring opioid analgesia were randomized to receive preoperative oral morphine (100 mcg·kg −1, 200 mcg·kg −1, 300 mcg·kg −1 ). Blood sampling for morphine assay was performed at 30, 60, 90, 120, 180, and 240 min. Morphine serum concentrations were determined by liquid chromatography–mass spectroscopy and pharmacokinetic parameters were calculated using nonlinear mixed effects models. Current data were pooled with published time–concentration profiles from children ( n = 1059, age 23 weeks postmenstrual age – 3 years) administered intravenous morphine, to determine oral bioavailability (F), absorption lag time (TLAG ), and absorption half‐time (TABS ). These parameter estimates were used to predict concentrations in children given oral morphine (100, 200, 300, 400, 500 mcg·kg −1 ) at different dosing intervals (3, 4, 5, 6, 8, 12 h). Results: The oral morphine formulation had F 0.298 (CV 36.5%), TLAG 0.45 (CV 63.6%) h and TABS 0.71 (CV 55%) h. A single‐dose morphine 100 mcg·kg −1 achieved a mean CMAX 10 mcg·l −1 . Repeat 4‐hourly dosing achieved mean steady‐state concentration 13–18 mcg·l −1 ; concentrations associated with good analgesia after intravenous administration. Serum concentration variability was large ranging from 5 to 55 mcg·l −1 at steady state. Conclusions: Oral morphine 200 mcg·kg −1 then 100 mcg·kg −1 4 h or 150 mcg·kg −1 6 h achieves mean concentrations associated with analgesia. There was high serum concentration variability suggesting that respiration may be compromised in some children given these doses. Abstract :